The role of supportive HRM practices in promoting work engagement: a study in statutory body - Marina, Nawi (2019)
This study aims to identify the relationship between Human Resource Practices (participative in decision making, fair rewards, and supervisor support) and work engagement. The sample of this study was clerical staff in one of the Statutory Body. There are 124 clerical staffs participated in this study. The method used to analyse the data is Statistical Package for Social Sciences 22.0 (SPSS). The findings of this study showed that only participative in decision making was significant with work engagement. According to the findings, limitations of this study and suggestions for future study were put forward.